A colorimetric hydrogen sulfide sensor based on gellan gum-silver nanoparticles bionanocomposite for monitoring of meat spoilage in intelligent packaging. (30th August 2019) - Zhai, Xiaodong; Li, Zhihua; Shi, Jiyong; Huang, Xiaowei; Sun, Zongbao; Zhang, Di; Zou, Xiaobo; Sun, Yue; Zhang, Junjun; Holmes, Melvin; Gong, Yunyun; Povey, Megan; et al.
Highlights: Ag nanoparticles (AgNPs) were green synthesized by using gellan gum (GG). GG-AgNPs show good sensitivity and selectivity towards H2 S. GG-AgNPs presented visible color changes when used to monitor meat spoilage. GG-AgNPs should have great potential for application in intelligent packaging. Abstract: A colorimetric hydrogen sulfide (H2 S) sensor based on gellan gum capped silver nanoparticles was developed to real-time monitor meat spoilage. The colorimetric sensor strategy was attributed to the ultrastrong binding ability of Ag with H2 S to form Ag2 S. The sensor enables the analysis of H2 S with a limit of detection (LOD) of 0.81 μM, and it exhibited excellent selectivity toward H2 S against other volatile components generated from chicken breast and silver carp during spoilage. By these virtues, the sensor presented visible color changes from yellow to colorless by in situ and nondestructively sensing H2 S generated from chicken breast and silver carp in a packaging system. This strategy provided a simple but useful, non-destructive, robust, cost-effective, and user-friendly platform to real time monitor meat spoilage for intelligent food packaging.